Determinación del umbral de lactato en el entrenamiento en futbolistas - Caicedo Valderrama, Cristhian Javier (2023)
This project investigation is called Determination Lactatu Umbral of Training deports Umbral. It is a project destined to develop the physical resistance to take Lactatu more efficacy. In this project, we did a test called Course Navete. We also made a pre-test, a control, and a post-test. This test was made on 25 futbol amateurs deports, all of them from 8vo semester pedagogy physical activity and sports of Chimborazo Nacional University; the objective was to analyze the lactate level and vital anaeróbico control level test blood and the final distance. For this investigation, we did two weekly training sessions lasting 24 hours, agreeing on intense exercises, resistance anaeróbica, fasting rain, medium duration, and completion. We have done planning of working, sharing times, relaxing, checking of frequency cardiac, streaming, al relax again. To check the blood lactate level, we have done the Course Navete test to take the maximum level of oxygen and the distance followed. We need small strips put on a drop of blood to do this. This investigation is to know the status of lactate umbral in the blood at the most hit level people have when they exercise when people can not tolerate the physical condition because the lactate level is too high in the blood, and the people could collapse.